2005
DOI: 10.1590/s1678-77572005000200004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of rules employed for calculation of pediatric drug dosage

Abstract: The present study was conducted to evaluate the utilization of Clark's, Salisbury and Penna's rules and the Body Surface Area (BSA) formula for calculation of pediatric drug dosage, as well as their reliability and viability in the clinical use. These rules are frequently cited in the literature, but much controversy still exists with regards to their use. The pediatric drug dosage was calculated by utilization of the aforementioned rules and using the drugs Paracetamol, Dipyrone, Diclofenac Potassium, Nimesul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…A study carried out by Elias GP et al, showed that standard doses calculated by Clark's formula for amoxicillin and erythromycin was not statistically significant (p>0.05) in three groups of children, group 1: age 1-3 years, group 2: age 3-5 years and group 3: age 6-12 years. 21 This finding is similar to our study. In a study by Lesar TS et al, showed that errors most commonly involved children (69.5%) and that too because of antibiotics (53.5%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A study carried out by Elias GP et al, showed that standard doses calculated by Clark's formula for amoxicillin and erythromycin was not statistically significant (p>0.05) in three groups of children, group 1: age 1-3 years, group 2: age 3-5 years and group 3: age 6-12 years. 21 This finding is similar to our study. In a study by Lesar TS et al, showed that errors most commonly involved children (69.5%) and that too because of antibiotics (53.5%).…”
Section: Discussionsupporting
confidence: 93%
“…The many calculations required in paediatrics to do weight based dosing may be an important factor contributing to the high rates of prescribing errors There was lack of published studies on dose calculation of different antihistaminic drugs in paediatric patients. In our study there was statistical significant difference in prescribed and standard doses of paracetamol which was similar to the study carried out by Elias GP et al 21 They calculated standard dose of paracetamol with the formula based on body surface area and found out it was statistically significantly different than the prescribed dose. It was much closer to the hepatotoxic dose of paracetamol for children.…”
Section: Discussionsupporting
confidence: 89%
“…Dosages based on the body weight are believed to be insufficient for the achievement of proper serum concentration of most drugs, the body surface being the most valid basis for dosage, since it is related to some physiological functions that account for the differences in pharmacokinetics in patients of different ages. 4 The British National Formulary (BNF), Martindale's Pharmacopoeia and many other reference textbooks state that the most reliable methods for calculation of children's drug doses are those based on BSA. 5 The average number of drugs per prescription 2.92 in our study has been similar to the reported figure of 2.9 in another study conducted in Mumbai.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a FDA-predicted dose model for warfarin, at first, and thereafter adjusted the recommended dose in each child, based on the body surface area. Clarcks, Salisbary, and Pennas formulations ( 31 ) showed a moderate association between the predicted warfarin dose, based on genotyping, and the stable anticoagulation dose (r = 0.5, P <0.001). The other studies have demonstrated similar results in their studies ( 18 , 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to warfarin and recommended dose, based on the genotyping results, were reported by genetic laboratory, considering the international warfarin pharmacogenetics consortium algorithms ( Tables 1 and 2 ) ( 30 ). Thereafter, the required dose of warfarin in each pediatric patient was determined, considering the dose recommended by genotyping and adjusted according to the patient’s height, weight, and body surface area, using the Pennas, Salisbary, and Clarks formula ( 31 ).…”
Section: Methodsmentioning
confidence: 99%